Toward a Better Worldliness : Ecology, Economy, and the Protestant Tradition - Rowe, Terra Schwerin (Book collections on Project MUSE., 2017)
Five hundred years ago the Protestant Reformation inspired profound theological, ecclesial, economic, and social transformations. But what impact does the Protestant tradition have today? And what might it have? This volume addresses such questions, focusing on the economic and ecological implications of the Protestant doctrine of grace. In the late twentieth-century, a number of Protestant scholars countered Max Weber's famous work on Protestantism and capitalism by arguing that Calvin and Luther were prophetic critics of early capitalist practices. While acknowledging the importance of this scholarship, Terra Rowe argues that a more nuanced approach is necessary. This narrative tends to purify Protestantism of capitalist beginnings and does not account for compelling arguments articulated by proponents of Radical Orthodoxy tying Protestantism--and Protestant grace in particular--to capitalism. These debates now emerge with increasing urgency in the face of growing economic injustice and overwhelming evidence of an ecologically unsustainable economic system, demonstrated most potently by climate change. In the spirit of ecotheologies resonating with the best of the Reformation tradition, this book develops a fresh reading of Luther's theology of grace and his economic ethics in conversation with current reflections on concepts of the gift and gifting practices.